Peran Unit Usaha Kampung Marketer Dalam Mengatasi Pengangguran Dan Urbanisasi Untuk Membentuk Ketahanan Pribadi Pemuda Desa Tamansari, Kecamatan Karangmoncol, Kabupaten Purbalingga, Provinsi Jawa Tengah - Wijaya, Placenta Abshar; Suprihanto, John; Riyono, Bagus (Universitas Pendidikan Ganesha, 2022)
The aims of this research include: (1) To analyze the role of the business unit of the Kampung Marketer (Marketer Village) in managing the unemployment and urbanization among the youths in Tamansari Village, Karangmoncol District, Purbalingga Regency, Central Java Province; (2) To evaluate the impacts of the business unit of a Kampung Marketer in building the personal resilience among the youths in Tamansari Village, Karangmoncol District, Purbalingga Regency, Central Java Province. This is a descriptive-qualitative research. The technique in collecting data in this research was conducted through interview, observation, documentation and searching online data. The analysis tool in this research used the descriptive-qualitative analysis and comparative analysis.The results of this research showed that: (1) there were a number of roles of the Business Unit of Kampung Marketer in managing the unemployment and urbanization among the youths in Tamansari Village, Karangmoncol District, Purbalingga Regency, Central Java Province, namely creating massive employment opportunities for youth in the village and of course providing the ability for young people to be self-employed; (2) There was an impact on the role of Business Unit of Kampung Marketer on the personal resilience building among the youths of Tamansari Village, Karangmoncol District, Purbalingga Regency, Central Java Province, i.e. in the aspects of self-confidence, responsibility, togetherness, independence, adhering to principles, and perseverance.